2019
DOI: 10.2474/trol.14.155
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ionic Liquid Type of Lubricant for Magnetic Disk Media

Abstract: The ionic liquid (IL) having a short perfluorether group and a hydroxy group was synthesized newly. The monolayer thickness of the IL and Z-Tetraol (Molecular Weight: approximately 2300) was 1.2 nm and 1.8 nm respectively which is measured by their spreading profiles experimentally. The adhesion and friction force of the lubricant thin film were measured by pin-on-disk microtribotester. While the adhesion force of Z-Tetraol increase with decreasing film thickness, the IL exhibits very small adhesion forces des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A small adhesion force was obtained which is critical for sustaining an ultra-low and stable flight of the slider head. While the adhesion force of Z-Tetraol increased with decreasing lubricant thickness, the IL exhibited a smaller adhesion force at thinner thickness [22]. This study demonstrated the feasibility of an IL for application as a lubricant for magnetic disk media.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…A small adhesion force was obtained which is critical for sustaining an ultra-low and stable flight of the slider head. While the adhesion force of Z-Tetraol increased with decreasing lubricant thickness, the IL exhibited a smaller adhesion force at thinner thickness [22]. This study demonstrated the feasibility of an IL for application as a lubricant for magnetic disk media.…”
Section: Introductionmentioning
confidence: 67%
“…The monolayer thickness of Z-Dol decreases with a decrease in MW. In our previous study [22], the monolayer thickness of Z-Tetraol 2000s (MW: 2300) was Table 1 Pin-on-disk microtribotest conditions Fig. 7 Schematic of the change in total load force on the rotating disk and corresponding motion of pin and the disk.…”
Section: Terrace Flowmentioning
confidence: 99%